Electrospun polyhydroxybutyrate and poly(L-lactide-co-ε-caprolactone) composites as nanofibrous scaffolds - Daranarong D. (Hindawi Publishing Corporation, 2014)
Electrospinning can produce nanofibrous scaffolds that mimic the architecture of the extracellular matrix and support cell attachment for tissue engineering applications. In this study, fibrous membranes of polyhydroxybutyrate (PHB) with various loadings of poly(L-lactide-co- ε -caprolactone) (PLCL) were successfully prepared by electrospinning. In comparison to PLCL scaffolds, PLCL blends with PHB exhibited more irregular fibre diameter distributions and higher average fibre diameters but there were no significant differences in pore size. PLCL/PHB scaffolds were more hydrophilic (<120°) with significantly reduced tensile strength (ca. 1 MPa) compared to PLCL scaffolds (150.9 ± 2.8 ° and 5.8 ± 0.5 MPa). Increasing PLCL loading in PHB/PLCL scaffolds significantly increased the extension at break, (4-6-fold). PLCL/PHB scaffolds supported greater adhesion and proliferation of olfactory ensheathing cells (OECs) than those exhibiting asynchronous growth on culture plates. Mitochondrial activity of cells cultivated on the electrospun blended membranes was enhanced compared to those grown on PLCL and PHB scaffolds (212, 179, and 153%, resp.). Analysis showed that PLCL/PHB nanofibrous membranes promoted cell cycle progression and reduced the onset of necrosis. Thus, electrospun PLCL/PHB composites promoted adhesion and proliferation of OECs when compared to their individual PLCL and PHB components suggesting potential in the repair and engineering of nerve tissue. © 2014 Donraporn Daranarong et al.